1994
DOI: 10.1007/bf01467915
|View full text |Cite
|
Sign up to set email alerts
|

Tibial attachment area of the anterior cruciate ligament in the extended knee position

Abstract: Knowledge of the anatomy of the anterior cruciate ligament (ACL), including its course and orientation in relation to the roof of the intercondylar fossa, is a prerequisite for successful intra-articular ACL reconstruction. To attain precision placement of the tibial attachment site and to avoid graft/roof conflict in the extended knee position, we assessed the anteroposterior tibial insertion of the ACL in the midsagittal plane of the extended knee. We measured the anterior-posterior (AP) limits and the cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
145
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(156 citation statements)
references
References 46 publications
10
145
0
1
Order By: Relevance
“…6). Like the normal ACL [19,25,30] the anterior surface of the graft should graze and be parallel to the slope of the intercondylar roof with the knee in maximum extension [19]. For the graft not to lie anterior to the anterior edge of the normal ACL, the tibial tunnel must be positioned in the posterior half of the normal ACL insertion [19].…”
Section: Five Factors Contributing To Roof Impingementmentioning
confidence: 99%
“…6). Like the normal ACL [19,25,30] the anterior surface of the graft should graze and be parallel to the slope of the intercondylar roof with the knee in maximum extension [19]. For the graft not to lie anterior to the anterior edge of the normal ACL, the tibial tunnel must be positioned in the posterior half of the normal ACL insertion [19].…”
Section: Five Factors Contributing To Roof Impingementmentioning
confidence: 99%
“…However, the validity and reliability of these measurement techniques have not been established. We measured the location of ACL grafts, using Staubli's technique (Staubli and Rauschning 1994) for the tibia, and a modification of Harner's technique (Harner et al 1994 ) for the femur. We found that the tibial and femoral graft positions as assessed on postoperative radiographs differed significantly from the graft positions measured on intraoperative radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with Stä ubli and Rauschning [26] a target value of 43% was assumed and a tolerance of ±4% accepted [27] (Fig. 3).…”
Section: Methodsmentioning
confidence: 99%